Pandangan Hukum Ekonomi Syariah Terhadap Akad dalam Transaksi Jual Beli Jamu : Studi Kasus di Toko Bina Raga Bondowoso - Fawaid Fawaid (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
The Researchers use qualitative research methods, covering primary and secondary data sources, data collection techniques of observation, interviews, and documentation, data analysis techniques of editing and organizing, verifying data testing, and research stages. All these researchers used to find results. Bondowoso Bina Raga store is a store that sells powdered herbs, concoctions, and medicines. In running his business, the owner of the shop instituted a provision that was made that everything purchased and taken out of the store could not be returned, so that all the customers making the herbal purchase transactions in the shop agreed to the provision.